Aqueous extraction of tomato seed oil using combination of ohmic heating and microwave heating as pretreatment - Sangeetha Karunanithi; Rakesh Kumar Gupta (Food Physics)
This study aimed to investigate the effect of ohmic (OH) and microwave heating (MH) pre-treatments on the aqueous extraction of tomato seed oil. As these thermal techniques disrupt the cell structure resulting in enhanced leaching, extractability was expected to be increased. Aqueous phase extraction of tomato seed pretreated with OH (14 V/cm), MH (540 W) and combination of ohmic heating and microwave heating (OH+MH) to compare the oil extractability. Physiochemical parameters have been determined for the extracted oil showing significant differences (p <0.01). The extractability of the oil was more in OH+MH comparing with OH and MH pre-treatments separately. SEM images of OH+MH treated samples showed the cellular damage resulting in high oil recovery. GCMS analysis of the oil samples disclosed the presence of linoleic acid and oleic acid as major contributors in OH+MH (52.15 %; 27.74 %) samples compared with the control (42.05 %; 12.14 %). Therefore, combination of ohmic heating and microwave heating is a novel green approach to improving oil extractability from tomato seeds because it combines efficient electrical and microwave energy, reducing processing time and energy consumption while minimizing the use of chemical solvents. Practical application: The research was conducted to utilize the waste from tomato processing industry. The tomato seed having an adequate amount of oil. The extraction process was done using water as a solvent. This can be probably eliminating the problem associated with organic solvents e.g. hexane causing an environmental problem, but the lower oil yield was overcome with the help of the pretreatment process. The emerging technologies namely ohmic and microwave were used as a pretreatment to enhance the lower extractability of oil. These technologies have more advantages in terms of least energy utilization, rapid processing time, solvent free extraction and enhanced quality of the oil. This research helps to maximize utilization of tomato seed waste to confer worthwhile byproduct at a large-scale level.